Somatic cell count and type of intramammary infection impacts fertility from in vitro produced embryo transfer - Barbosa, L. F. S. P. [UNESP]; Oliveira, W. V. C. [UNESP]; Pereira, M. H. C. [UNESP]; Moreira, M. B.; Vasconcelos, C. G. C.; Silper, B. F.; Cerri, R. L. A.; Vasconcelos, J. L. M. [UNESP] (Elsevier B.V., 2018)
The objective of this study was to assess the impact of mastitis-causing bacteria and somatic cell count (SCC) on pregnancy per embryo transfer (P/ET) in Holstein-Gir crossbred (Girolando) lactating dairy cows. Cows (n = 1397) were subjected to a timed-embryo transfer protocol. Milk samples were collected two days before embryo transfer for SCC and bacteriological culture analyses. Pregnancy diagnosis was performed on days 31 and 66 after timed-embryo transfer. The animals were grouped according to the National Mastitis Council recommendations: Gram-positive environmental (EV+), Gram-negative environmental (EV-), Gram-positive contagious (C+), coagulase-negative staphylococci (CNS) and control (no bacterial growth). Additional analysis was made by categorizing bacteria based on degree of pathogenicity (Major or Minor). Bacterial growth reduced P/ET (P < .01) at both 31 and 66 days of gestation. The P/ET was lower (P < .05) at 31 days in EV- (30.1%) and EV+ (29.9%) groups and tended (P = .09) to be lower in the C+ group (36.6%) than the control group (44.0%). The P/ET from the Major group at 31 days of gestation was lower (P = .03) compared with the Minor and control groups (32.1 vs 41.1 vs 43.2%, respectively). Cows with SCC > 400,000 cells/mL had lower P/ET (P < .01) than animals with SCC < 200,000 cells/mL at both 31 (30.4% vs 40.8%) and 66 days (24.7% vs 32.2%) of gestation. Pregnancy loss was not different between bacterial isolates and SCC categories. Elevated SCC significantly reduced P/ET, whereas environmental agents and those with Major pathogenicity yielded the greatest reduction in NET. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Embryo transfer; Fertility; Intramammary infection; Mastitis; Somatic cell count